Exploring Active Sites in Nitrogen Doped Carbon Nanotube Based Electrocatalyst. (24th August 2017) - Chen, Ti; Takahashi, Shota; Waki, Keiko
Abstract : Nitrogen doped carbon based electrocatalysts showed relative high ORR activity compared with the conventional Pt/C catalysts. However, the active sites in nitrogen doped carbon catalysts still remain unclear. In this study we adopted the degradation and re- doping experiments to probe the active site in the nitrogen doped multiwalled carbon nanotube electrocatalysts. The electrochemical measurements and XPS analysis suggested that it is unlikely that the ORR active site in HA-N900 is pyridinic nitrogen itself or the carbon atom next to the pyridinic nitrogen.